EXPERIENCE OF APPLICATION OF A PORTABLE OPTICO – EMISSION SPECTROMETER FOR MONITORING OF CHEMICAL COMPOSITION OF HOT-ROLLED PRODUCTS TO IMPLEMENT THE CUSTOMER’S REQUIREMENTS - E. A. Kazakova; T. S. Birisen (Литьë и металлургия)
One of requirements of customers in the automotive industry is the guarantee of lack of intermix of various brands of steel in a mill process of manufacture. For ensuring implementation of this requirement, it is necessary to carry out monitoring of chemical composition of each bar just before shipment, after its packing and application of the required marking. An optimal solution of this problem is application of the portable optico-emission spectrometer allowing to carry out tests of samples directly in place of location.